Anti-Corruption Values Civilization Management Model in the Program of Strengthening Character Education in Public Primary Schools in Gorontalo Regency - Irmawati Duko Ishak (GoAcademica Research & Publishing, 2019)
This study is about a model of civilizing anti-corruption values in the implementation of programs to strengthen character education in public elementary schools in the district. Gorontalo. The main target of this research is to design a model of the civilization of anti-corruption values in the implementation of character education strengthening programs that can produce products in the form of books to guide educators, parents and the public, especially in Gorontalo district in implementing anti-corruption values which lead to the creation of anti-corruption characters. This research applies the research and development approach. This research also answers specific questions of practical problems through